A Strictly Dinuclear MnIII–GdIII Complex: Synthesis and Magnetic Properties. Issue 19 (31st May 2013) - Costes, Jean‐Pierre; Tuchagues, Jean‐Pierre; Vendier, Laure; Garcia‐Tojal, Javier
Abstract: A strictly heterodinuclear Mn III –Gd complex was prepared from a tripodal ligand and characterized by positive fast‐atom bombardment mass spectrometry, which evidenced replacement of a nitrato counterion by a monoethylcarbonato anion. Variable‐temperature direct current and alternating current studies confirm that the Mn III –Gd magnetic interaction is antiferromagnetic. Fitting of the magnetic susceptibility data yields an extremely weak interaction parameter J MnGd equal to –0.04 cm –1, along with a weak axial zero‐field splitting parameter D Mn = 0.1 cm –1 . This result confirms that a change in the manganese oxidation state, from Mn II to Mn III, corresponds to a radical transformation of the magnetic behavior of Mn–Gd, from a ferromagnetic to an antiferromagnetic interaction. In accordance with the magnetic behavior of Co II –Gd complexes previously studied (high‐spin and low‐spin Co II ions), the observed magnetic behavior change may be explained by the difference in the electronic occupancy of the Mn 3d x 2 – y 2 orbital, which is singly occupied for Mn II and vacant for Mn III . Abstract : The interaction between a 3d metal ion and Gd is antiferromagnetic if the 3d ion has no electron in its d x 2 – y 2 orbital, as evidenced by the dinuclear Mn III –Gd complex. This is in contrast to the ferromagnetic behavior of dinuclear Mn II –Gd complexes for which the 3d x 2 – y 2 orbital of Mn II is singly occupied. This result agrees with our hypothesis initially based on Co II low spin –Gd vs. Co II high spin –Gd complexes.